PEMBUATAN BIOETANOL DARI KUPASAN KENTANG (Solanum tuberosum L.) DENGAN PROSES FERMENTASI - Hasianna Purba, Devi Esteria; Suprihatin, Iryanti Eka; Laksmiwati, A.A.I.A. Mayun (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p21, 2016)
Ethanol fermented from potato peels is proposed as one alternative source of renewable energy called bioethanol. In this research bioethanol was produced through four stages namely acid hydrolysis, detoxification, fermentation and distillation. The acid hydrolysis process was carried out using sulphuric acid at 100 o C for 60 minutes. The detoxification process was carried out by adding NH 4 OH into the hydrolyzate prior to fermentation. Distillation was performed up to 100 o C and the distillate with the BP of 78-84 o C was determined for its ethanol content using gas chromatography. The ethanol produced from 5 grams of dried potato peels through fermentation for 4, 5, 6, and 7 days 3.54%; 4,85%; 5,35%; and 6.15% respectively.
Keywords: potato peels, acid hydrolysis, detoxification, fermentation, ethanol, bioethanol